Substituting Far-Red for Traditionally Defined Photosynthetic Photons Results in Equal Canopy Quantum Yield for CO2 Fixation and Increased Photon Capture During Long-Term Studies: Implications for Re-Defining PAR - Zhen, Shuyang; Bugbee, Bruce (Frontiers in Plant Science, 2020)
Far-red photons regulate shade avoidance responses and can have powerful effects on plant morphology and radiation capture. Recent studies have shown that far-red photons (700 to 750 nm) efficiently drive photosynthesis when added to traditionally defined photosynthetic photons (400-700 nm). But the long-term effects of far-red photons on canopy quantum yield have not yet been determined. We grew lettuce in a four-chamber, steady-state canopy gas-exchange system to separately quantify canopy photon capture, quantum yield for CO2 fixation, and carbon use efficiency. These measurements facilitate a mechanistic understanding of the effect of far-red photons on the components of plant growth. Day-time photosynthesis and night-time respiration of lettuce canopies were continuously monitored from seedling to harvest in five replicate studies. Plants were grown under a background of either red/blue or white light, each background with or without 15% (50 μmol m-2 s-1) of far-red photons substituting for photons between 400 to 700 nm. All four treatments contained 31.5% blue photons, and an equal total photon flux from 400 to 750 nm of 350 μmol m-2 s-1. Both treatments with far-red photons had higher canopy photon capture, increased daily carbon gain (net photosynthesis minus respiration at night), and 29 to 31% more biomass than control treatments. Canopy quantum yield was similar among treatments (0.057  0.002 moles of CO2 fixed in gross photosynthesis per mole of absorbed photons integrated over 400 to 750 nm). Carbon use efficiency (daily carbon gain/gross photosynthesis) was also similar for mature plants (0.61  0.02). Photosynthesis increased linearly with increasing photon capture and had a common slope among all four treatments, which demonstrates that the faster growth with far-red photon substitution was caused by enhanced photon capture through increased leaf expansion. The equivalent canopy quantum yield among treatments indicates that the absorbed far-red photons were equally efficient for photosynthesis when acting synergistically with the 400-700 nm photons.